Statically-Indeterminate SFRC Columns under Cyclic Loads - Abbas, Ali A.; Sharifah Maszura, Syed Mohsin; Cotsovos, Demetrios M.; Ruiz-Teran, Ana M. (Multi-Science Publishing, 2014)
The present study is aimed at examining the structural response of steel-fibre-reinforced concrete (SFRC) columns under reversed-cyclic loading, which were investigated by means of non-linear finite-element analysis (NLFEA). The focus was on investigating the potential of steel fibres in compensating for reduction in conventional transverse reinforcement [and thus the spacing between shear links was increased by 50% and 100% while the fibre volume fraction (Vf) was increased to 1%, 1.5%, 2% and 2.5%]. This is useful in situations where the latter is required in significant amounts (e.g. in seismic design) leading to congestion and practical difficulties in placing the links. The critical factor in the seismic response is the cyclic nature of the load, which is examined in the present research work. An interesting feature of the present research work is the consideration of statically-indeterminate SFRC columns, information on which is rare as previous research studies have focused on simply-supported beams. To address this, both indeterminacy and axial loads were considered in the present investigation. Calibration work was carried out using existing experimental data and good correlation was established between numerical and test results. Subsequently, parametric studies were carried out using the practical range of fibre dosages, which provided insight into how the steel fibres can help reduce the amount of conventional shear links.